Drawing the Map of Heaven : an African Writer in America. - Ojaide, Tanure (Malthouse Press, 2012)
The celebrated Nigerian writer Tanure Ojaide relates here his experience of living in the United States where he has been based teaching and writing since 1996. Drawing the Map of Heaven picks up where his earlier memoir, Great Boys. An African Childhood which charted his upbringing in Nigeria by his Grandmother, left off. Less a purely personal tale and more a story of the many other African immigrants in the United States Ojaide in the text uses ""we"" to speak collectively for a traditionally communal society now residing in an individualistic setting. As much a reflection of an African ba.